The Influence Of Organizational Culture And Organizational Commitment On Employee Performance At The Office Of Population And Civil Registration Of North Nias Regency - Indra Gunawan Zega; Palindungan Lahagu (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This research examines the influence of organizational culture and organizational commitment on employee performance at the Office of Population and Civil Registration of North Nias Regency. Using a quantitative approach, data were collected from 30 civil servants through questionnaires employing a Likert scale. Statistical analysis included validity and reliability tests, classical assumption tests, and hypothesis testing using t-test (partial) and F-test (simultaneous). Results indicate significant positive influences: organizational culture on employee performance (t-value=16.134 > t-table=2.048) and organizational commitment on employee performance (t-value=11.786 > t-table=2.048). Simultaneous test reveals both variables jointly influence employee performance (F-value=125.729 > F-table=3.328) with a coefficient of determination of 89%, indicating that 89% of employee performance variance is explained by organizational culture and organizational commitment, while 11% is influenced by other factors. The research identifies critical issues including inadequate implementation of service culture principles (smile, greeting, courtesy), declining responsiveness in civil document processing, and insufficient inter-employee collaboration. These findings emphasize the necessity for strengthening organizational culture practices and enhancing organizational commitment to improve service quality and employee performance in public sector institutions.